1973
DOI: 10.1002/1097-0142(197311)32:5<1236::aid-cncr2820320533>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Tumors of the urethra in men and women

Abstract: A study of urethral tumors in men and women has been made. The 3 most important tumors involving the male urethra are: 1. those arising in the meatus and parameatal area; 2. squamous cell cancer of the membranous urethra; and 3. transitional cell cancer of the prostatic urethra. The latter 2 respond poorly to any and all forms of therapy regardless of extent of ablative surgical attempt or radiation therapy dosage. Tire' latter prostatic urethral tumor is also hormone‐resistant. The most common tumors of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
1
3

Year Published

1978
1978
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(21 citation statements)
references
References 50 publications
0
17
1
3
Order By: Relevance
“…1 Obstructive symptoms due to a urethral mass or stricture are the usual presenting features. 2,3 Chronic irritation, infection, and trauma, including that from instrumentation used to relieve strictures, are the major predisposing factors. 1,2 In one series, 37% of patients had a history of venereal disease, 35% had stricture, and 7% had suffered trauma.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Obstructive symptoms due to a urethral mass or stricture are the usual presenting features. 2,3 Chronic irritation, infection, and trauma, including that from instrumentation used to relieve strictures, are the major predisposing factors. 1,2 In one series, 37% of patients had a history of venereal disease, 35% had stricture, and 7% had suffered trauma.…”
mentioning
confidence: 99%
“…1,2 In one series, 37% of patients had a history of venereal disease, 35% had stricture, and 7% had suffered trauma. 3 It has been reported that up to 88% of patients with urethral carcinoma have a history of urethral stricture. The most common site for stricture, the bulbomembranous urethra, is also the most common location for carcinoma.…”
mentioning
confidence: 99%
“…It has been regarded that urethral carcinoma is the only urological cancer that is more common in female than in male [14]. However, in a large population-based study, the incidence of primary urethral carcinoma is relatively higher in men and black population in the United State [2].…”
Section: Discussionmentioning
confidence: 99%
“…Only five cases have been reported inthe literature up to the end of December 1988.' Urothelial metaplasia or ectop-ic urothelium may explain the occurrence of transitional cell carcinoma in an area normally lined by squamous epithelium.2" However, the isolation of human papilloma virus type 6 RNA in three cases of Grade I papillary transitional cell carcinoma of the anterior urethra in association with condyloma acuminata raises the possibility of an active role for the virus in the pathogenesis of the lesion. 4 Here we report a case of transitional cell carcinoma of the anterior urethra presenting with features consistent with periurethral inflammation and review the related literature.…”
Section: Introductionmentioning
confidence: 99%